The Effect Of Agrarian Law In The Development Of Legal Politics In Indonesia (International Journal of Education and Literature, 2023)
This article examines the influence of agrarian law in the development of legal politics in Indonesia with a focus on issues of land ownership and human rights. This article explains that land ownership is often a source of conflict and disputes in Indonesian society, especially when land does not have clear certificates. The Basic Agrarian Law (UUPA) is the legal basis that provides guarantees for land rights for the people of Indonesia. The National Agrarian Operations Project Program (PRONA) is the government's effort to provide land certificates to people with economically weak groups. This article also reviews changes in legal political views in Indonesia following the transition from the New Order era to the reform era. During the New Order era, there were shackles in various sectors, including law and politics. However, during the reform period, efforts to restore Indonesia's image as a rule of law through changes in government policy were carried out concerning the 1945 Constitution and Pancasila. In the context of land ownership and human rights, this article underscores the need to protect the rights of rural communities and indigenous peoples whose ownership is inherited hereditary, regardless of the completeness of the ownership papers. This article examines the need for a balance between public interest and individual rights in the context of land ownership in Indonesia. In conclusion, this article presents a comprehensive analysis of the influence of agrarian law in the development of legal politics in Indonesia. By highlighting changes in legal politics, protection of human rights, and issues of land ownership,